Effect of storage time and temperature in the determination of serum and plasma biochemical parameters of Quarter horses - de Oliveira, Ágatha Ferreira Xavier; Raimundo, Juliana Macedo; Pires, Marcus Sandes; Amaro, Gleice Marques; Guimarães, Andresa; da Silva, Aline Tonussi; Botelho, Camila Flavia Magalhães; Machado, Carlos Henrique; de Almeida, Fernando Queiroz; Baldani, Cristiane Divan (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Oliveira A.F.X., Raimundo J.M., Pires M.S., Amaro G.M., Guimarães A., Silva A.T., Botelho C.F.M., Machado C.H., Almeida F.Q. & Baldani C.D. [Effect of storage time and temperature in the determination of serum and plasma biochemical parameters of Quarter horses.] Efeito do tempo e da temperatura de armazenamento na determinação de parâmetros bioquímicos séricos e plasmáticos de equinos Quarto de Milha. Revista Brasileira de Medicina Veterinária, 38(Supl.2):11-16, 2016. Departamento de Medicina e Cirurgia Veterinária, Universidade Federal Rural do Estado do Rio de Janeiro, BR 465, KM 47, Seropédica, RJ 23890-000, Brasil. E-mail: crisbaldani@gmail.com The aim of the present study was to evaluate the effect of storage time and temperature of serum and plasma on the determination of clinical biochemistry analytes in horses. Blood samples were taken from ten clinically healthy Quarter Horses, and analysis were performed immediately after obtaining the sample (time zero) and after 24 hours, 48 hours, 7, 15, 30, 60 and 90 days. Samples were evaluated at room temperature (16.6 to 29.6° C), refrigeration (4° C) and freezing (-20° C). Biochemical parameters analysed were urea, creatinine, creatine kinase (CK), aspartate aminotransferase (AST), alkaline phosphatase (ALP), glucose, lactate, total protein (TP) and albumin. All parameters were stable at room temperature for 24 hours. Under refrigeration conditions no significant differences (p> 0.05) were observed until the 30th day of analysis, with exception of albumin which demonstrated instability from day 15 . In frozen (-20° C) samples, albumin and AST were significantly unstable on 15 and 90 days (p <0.05) of analysis respectively, remaining the other analytes without significant changes for 90 days. The results showed considerable stability of biochemical parameters on serum or plasma, ensuring greater autonomy to veterinarians in sending samples to the clinical laboratory.